THE IMPORTANCE OF EXHIBITION MEDIA IN INCREASE OF EDUCATIONAL EFFICIENCY (International journal of artificial intelligence, 2024)
This article provides information about the role of didactic materials in increasing the effectiveness of pedagogical education.